Bibliometric Analysis of Journals, Authors and Topics Related to Indonesian Mosque Economics Listed in the Dimensions Database - Fanani, Achmad Zainal; Siregar, Saparuddin (Journal of Islamic Economics Literatures, 2024)
This bibliometric study analyzes the current state of research on the topic of "Mosque Economics Indonesia" published by journals over the past 10 years using the Dimensions database. The analysis focused on describing the characteristics and trends of keywords, authors, and journals. The data analyzed came from 114 research publications in Dimensions. The search used to establish the research dataset was conducted on June 12, 2024. Descriptive qualitative methods were used, and bibliometric analysis was conducted using Vosviewer to generate bibliometric maps. Based on bibliometric keyword mapping, there are 2 clusters that can be a research path with topics related to Mosque economics Indonesia: (1)worship and Mosque economics Indonesia and (2)economics empowerment. While the most popular keywords used are "mosque", "Muslims", "worship", 'fact', 'welfare' and 'economics empowerment". Furthermore, the research found that in bibliometric author mapping the authors who published the most research with the theme "Mosque Economic Indonesia" were Arjmand, Reza, Mirsafa, Masaumeh, Talibi, and Zeinab. This research illustrates that the trend of keywords, journals, and authors of articles on the topic of "Mosque Economics Indonesia" has been discussed quite a lot, but this theme has the potential to continue to be developed.